Scanning probe microscopy studies on the adsorption of selected molecular dyes on titania - Prauzner-Bechcicki, Jakub S.; Zajac, Lukasz; Olszowski, Piotr; Jöhr, Res; Hinaut, Antoine; Glatzel, Thilo; Such, Bartosz; Meyer, Ernst; Szymonski, Marek (Beilstein Journal of Nanotechnology, 2016)
Titanium dioxide, or titania, sensitized with organic dyes is a very attractive platform for photovoltaic applications. In this context, the knowledge of properties of the titania–sensitizer junction is essential for designing efficient devices. Consequently, studies on the adsorption of organic dyes on titania surfaces and on the influence of the adsorption geometry on the energy level alignment between the substrate and an organic adsorbate are necessary. The method of choice for investigating the local environment of a single dye molecule is high-resolution scanning probe microscopy. Microscopic results combined with the outcome of common spectroscopic methods provide a better understanding of the mechanism taking place at the titania–sensitizer interface. In the following paper, we review the recent scanning probe microscopic research of a certain group of molecular assemblies on rutile titania surfaces as it pertains to dye-sensitized solar cell applications. We focus on experiments on adsorption of three types of prototypical dye molecules, i.e., perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA), phtalocyanines and porphyrins. Two interesting heteromolecular systems comprising molecules that are aligned with the given review are discussed as well.
Keywords: dye molecules; perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA); phtalocyanines; porphyrins; rutile; scanning probe microscopy; scanning tunneling microscopy (STM); titanium dioxide (TiO2)